2017
DOI: 10.3390/en10111908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Obstacles on the Propagation of Premixed Methane-Air Flames in a Half-Open Tube

Abstract: Abstract:To understand the propagation characteristics of methane-air deflagration flames and in an obstacle-filled tube, a high-speed color video camera, photoelectric sensors, and pressure transducers were used to test the deflagration flame propagating parameters. The tests were run in a 1500 mm long plexiglass tube with a 100 × 100 mm square cross-section. The obstacles included four types of repeated baffles and five forms of solid structure obstacles. The results showed that: (1) the flame front was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Yu et al 14 experimentally studied the influence of a single hollow obstacle on the characteristics of methane-air explosions and found that fewer sides of the hollow shape led to a stronger acceleration effect. Wang et al 17 studied the effect of plate and solid obstacles on explosion flames and showed that abrupt edges or irregular shapes of obstacles can promote flame propagation. Di Sarli et al 18 found that a single obstacle with a larger axial length is more likely to cause higher explosion pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al 14 experimentally studied the influence of a single hollow obstacle on the characteristics of methane-air explosions and found that fewer sides of the hollow shape led to a stronger acceleration effect. Wang et al 17 studied the effect of plate and solid obstacles on explosion flames and showed that abrupt edges or irregular shapes of obstacles can promote flame propagation. Di Sarli et al 18 found that a single obstacle with a larger axial length is more likely to cause higher explosion pressure.…”
Section: Introductionmentioning
confidence: 99%